Peran Lembaga PAUD Pertiwi Bulukumba Dalam Mengembangkan Kemampuan Sosialisasi Anak di Keluarga (Suatu Tinjauan Sosiologi) - Risfaisal, Risfaisal (DISCOURSE: Indonesian Journal of Social Studies and Education, 2025)
This study aims to analyze the social role of the Early Childhood Education (PAUD) Institution in the process of socializing children in the family environment. The focus of the research is to understand the extent to which PAUD Institutions affect children's socialization abilities, including interaction, communication, and self-adjustment in the family. The research method used is qualitative with a descriptive approach. Data was collected through observation, in-depth interviews with parents, PAUD teachers, and documentation studies within the PAUD Institute. The results of the study show that PAUD Institutions play a significant role in improving children's socialization skills, such as independence, cooperation, and communication skills. This research confirms that the success of children's socialization process is significantly influenced by the synergy between the role of the family (especially parents) and PAUD institutions. In this critical phase of early development, children need consistent role models and educational guidance to internalize social values appropriately. In addition, children's participation in PAUD activities also helps parents in understanding more effective parenting styles to support children's social development. The implication of this study is the importance of the role of PAUD Institutions as family partners in shaping children's character and social skills from an early age.